CYBERGUARD: A Mobile Cyberbullying Detector - et.al, Siok Yee Tan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social media is something that is used by a lot of people in Malaysia, especially among youths today. Social media can come in many different platforms such as facebook and twitter. However, due to the convenience given, a person can send a message to another person through social media in the blink of an eye. Many cases of bullying occur online, and these cases are known as cyber bullying. Cyber bullying happens when a person bullies and harasses another user online by sending harassing messages such as messages with rude words or messages with sexual harassment elements. Cyber bullying can be dangerous, affecting a person's emotion, especially among youths, because they have no experience with cyber bullying and doesn't know how to overcome this problem. As such, an android-based application named cyber guard has been developed to overcome this problem. This application is developed by connecting the user's twitter profile to retrieve the messages from the user's twitter messages. This application will alert the user if the application detects a negative implication's word retrieved from their twitter account. This application will also explain the meaning of the negative implication's word and their threat level. For users experiencing cyber bullying, the application provides advice and ways to overcome cyber bullying issues. Fifteen users have tested this application and the application has received good feedbacks from the users. This application is vital to everyone, especially youths, to know whether they are being cyber bullied and the steps that can be taken to overcome it.